Equilibri e squilibri demografici tra Bacino Mediteraneo, Unione Europea e Mondo Arabo - Luigi Di COMITE; Simona GIORDANO (Polis: Revista de Stiinte Politice, 2014)
With this research paper the authors do a pertinent analysis of the demographic balances and imbalances and their influence on the international migration phenomenon, in regards to the Mediterranean Basin, the European Union and the Arab world. Starting from a fact, that the aforementioned geographic space includes a population of approximately one billion people, the authors identify the risk zones and analyze the demographical aspects through the particular indicators belonging to this domain: fecundity, mortality, population ageing, internal and external mobility of the population, the purpose being to underline the new socio-cultural processes with which this ancient space of culture and civilization will be interacting in the future decades.